Measuring the Impact of Hedonic Motivation, Smart Shopper Perception, Location-Based Coupon Attitude on Intention of Use Location-Based Coupon - Anneu Suryani; Agus Rahayu; Puspo Dewi Dirgantari (Dinasti Publisher, 2023)
Increasing use of GPS on mobile devices, the format of direct marketing strategy is also developing, and the location-based coupon is the example of this strategy. This study aims to analyze consumer attitudes toward location-based coupons on mobile devices and their intention of use the location-based coupon for shopping. Simple random sampling is used for the sampling method, a 1 – 5 Likert scale questionnaire is used for collecting the data. The results show that hedonic motivation, and smart-shopper perception has a positive effect towards intention of use location-based coupon through location-based coupon attitudes. Even so, the impact is not big because there are several variables excluding of this study that might influence it.